Pulsed beam of extremely large helium droplets. (December 2017) - Kuma, Susumu; Azuma, Toshiyuki
Highlights: A cryogenic pulsed valve succeeds in producing micron-size huge helium droplets. Realization of the supercritical expansion is clearly indicated firstly in pulsed form. Other pulsed techniques should be easily combined for exploring new nano-science. Abstract: We generated a pulsed helium droplet beam with average droplet diameters of up to 2  μ m using a solenoid pulsed valve operated at temperatures as low as 7 K. The droplet diameter was controllable over two orders of magnitude, or six orders of the number of atoms per droplet, by lowering the valve temperature from 21 to 7 K. A sudden droplet size change attributed to the so-called "supercritical expansion" was firstly observed in pulsed mode, which is necessary to obtain the micrometer-scale droplets. This beam source is beneficial for experiments that require extremely large helium droplets in intense, pulsed form.